Developmental delay in young children with sleep-disordered breathing before and after tonsil and adenoid surgery. (June 2016) - Goldstein, Nira A.; Gorynski, Michael; Yip, Candice; Harounian, Jonathan; Huberman, Harris; Weedon, Jeremy
Abstract: Objective: Our objective was to determine the developmental status of young children with sleep-disordered breathing (SDB) as measured by the Ages and Stages Questionnaire (ASQ-3) and to evaluate improvement after treatment. Methods: The ASQ-3 was completed at entry, 3 months and 6 months after adenotonsillectomy or adenoidectomy. The questionnaire consists of 30 items that assess five domains: communication, gross motor, fine motor, problem solving and personal-social. Domain scores were compared with normative values: abnormal ≥2 SDs and borderline ≥1 but <2 SDs below the mean. Results: 80 children, mean (SD) age 3.0 (0.94) years, 62.5% male, 77.5% African American, were enrolled. Median (range) apnea–hypopnea index (AHI) was 12.6 (1.4–178.5). At entry, 22 (27.5%) children scored in the abnormal range in at least one developmental area and an additional 23 (28.8%) had at least one borderline score. A generalized linear model including gender, AHI, maternal education and prematurity showed that only prematurity was an independent predictor of at least one abnormal or borderline entry score (likelihood ratio test p  < 0.001). Adjusting for covariates and excluding children with a history of prematurity, the prevalence of at least one abnormal or borderline score (based on 112 observations of 70 children) was estimated at 49% (95% CI [37, 62]) at baseline; 34% (95% CI [17, 56]) at 3 months; and 22% (95% CI [10, 41]) at 6 months. Post-hoc pairwise comparison of time points showed the baseline versus 6-month difference to be statistically significant ( p  = 0.015). Conclusions: The 27.5% baseline prevalence of abnormal ASQ scores in children with SDB indicates it is a risk factor for developmental delay. Significant improvements in score classifications were found 6 months after surgery.